A Novel de Novo Mutation in the CD40 Ligand Gene in a Patient With a Mild X-Linked Hyper-IgM Phenotype Initially Diagnosed as CVID: New Aspects of Old Diseases - França, Tábata T.; Leite, Luiz F. B.; Maximo, Tiago A.; Lambert, Christiane G.; Zurro, Nuria B.; Forte, Wilma C. N.; Condino-Neto, Antonio (Frontiers in Pediatrics, 2018)
Mutations in the CD40 ligand (CD40L) gene (CD40LG) lead to X-linked hyper-IgM syndrome (X-HIGM), which is a primary immunodeficiency (PID) characterized by decreased serum levels of IgG and IgA and normal or elevated IgM levels. Although most X-HIGM patients become symptomatic during the first or second year of life, during which they exhibit recurrent infections, some patients exhibit mild phenotypes, which are usually associated with hypomorphic mutations that do not abrogate protein expression or function. Here, we describe a 28-year-old man who initially presented with recurrent infections since the age of 7 years, when he exhibited meningitis caused by Cryptococcus neoformans. The patient had no family history of immunodeficiency, and based on clinical and laboratory presentation, he was initially diagnosed with common variable immunodeficiency (CVID). In subsequent years, he displayed several sporadic episodes of infection, including pneumonia, pharyngotonsillitis, acute otitis media, rhinosinusitis, fungal dermatosis, and intestinal helminthiasis. The evaluation of CD40L expression on the surface of activated CD3+CD4+ T cells from the patient showed decreased expression of CD40L. Genetic analysis revealed a novel de novo mutation consisting of a 6-nucleotide insertion in exon 1 of CD40LG, which confirmed the diagnosis of X-HIGM. In this report, we describe a novel mutation in the CD40L gene and highlight the complexities of PID diagnosis in light of atypical phenotypes and hypomorphic mutations as well as the importance of the differential diagnosis of PIDs.